Entrepreneurial Resilience: Strategies for MSMEs to Navigate Uncertainties and Challenges in Contemporary Markets - Susilawati, Made (International Journal of Business, Law, and Education, 2024)
In the face of contemporary market uncertainties and challenges, the resilience of Micro, Small, and Medium Enterprises (MSMEs) is critical for their sustainability and growth. This study investigates the strategies that MSMEs can adopt to enhance their resilience, focusing on four key dimensions: strategic agility, operational resilience, financial resilience, and socio-emotional resilience. Utilizing a mixed-methods approach, the research integrates quantitative data from surveys and qualitative insights from interviews with MSME stakeholders. The findings reveal that strategic agility and operational resilience significantly contribute to MSME performance, enabling firms to adapt and maintain business continuity. Financial resilience also plays a crucial role, highlighting the importance of sound financial management and access to diverse funding sources. While socio-emotional resilience is less directly linked to performance outcomes, it is vital for fostering a supportive and innovative organizational culture. The study provides comprehensive insights and practical recommendations for MSMEs, policymakers, and practitioners to build resilient business practices and ensure sustainable growth.